Effects of coral restoration on fish communities: snapshots of long‐term, multiregional responses and implications for practice. Issue 5 (11th August 2020) - Hein, Margaux Y.; Beeden, Roger; Birtles, R. Alastair; Chase, Tory J.; Couture, Fanny; Haskin, Elouise; Marshall, Nadine; Ripple, Kayla; Terry, Lisa; Willis, Bette L.; Willis, Reanna; Gardiner, Naomi M.
Abstract : Coral restoration is widely used around the world to address dramatic declines in coral cover; however, very few studies have looked specifically at the temporal response of fish assemblages (i.e. abundance and diversity) to coral restoration. Several critical reef functions and processes are driven by fishes, thereby making their recovery and responses around restoration structures key indicators of success. This study evaluates fish abundance and community composition on restoration plots following 8–12 years of restoration activity, in four locations (two Caribbean and two Indo‐Pacific). Responses were very complex with region‐, site‐, and body size‐specific patterns. Overall, fish abundance only increased in Indo‐Pacific sites where damselfish responded positively to increased coral cover and topographic complexity. Restoration effects on other fish families and particularly on larger bodied reef fish were negative or neutral at all locations. If restoration initiatives are going to substantively improve the condition and recovery of degraded reef fish communities, restoration efforts need to be planned, designed, and monitored based on fish‐specific habitat requirements and locally specific community dynamics.